Teknologi Artefak Tulang Toala dan Persentuhannya dengan Penutur Austronesia di Situs Liang Uttangnge 1 dan Situs Liang Sibokoreng: Teknologi artefak tulang Toala dan pendukung budaya neolitik di Mallawa, Maros - Muhammad Saiful Andi; nfn. Hasanuddin; nfn. Bernadeta; Iwan Sumantri; nfn. Supriadi; nfn. Isbahuddin; Yulastri Yulia; Khaidir Sirajuddin (Berkala Arkeologi, 2023)
This paper examine bone artefact from the Liang Uttangnge 1 Site (3.300 BP) and Liang Sibokoreng Site (8.160 BP). This paper aims to determine the semilarities and different in bone artefact technology from the two site and to determine the influence that occcurs between the two culture in Liang Uttangnge 1. The method used is macroscopic identification using a loop and dinolite which include the source material and manufacturing trace (scraping, shaving, and grinding). This results are then analyzed to find out the semilarities and differents in technology from the two culture phases. This study explains that there is no difference in the technology of processing bone artefact from the Toala culture phase and the culture phase contact of the Toala and Austronesian culture. Therefore, the ifluences the Toala culture on the use of bone artefacts at the time of contact between Toala and Austronesian still exists.